HUBUNGAN TINGKAT STRES MASA PANDEMI COVID-19 DENGAN KECEMASAN PADA MAHASISWA/I FAKULTAS KEDOKTERAN UNAYA - Edy Cahyady; Niska Alfisyahrin (Jurnal Sains Riset, 2021)
COVID-19 is a virus that causes disease in humans and animals. Respiratory tract infections usually occur in humans ranging from common ones such as the flu to serious ones such as COVID-19, which is currently becoming a worldwide pandemic. The impact of this pandemic for all universities in Indonesia has caused all learning activities that are usually used face-to-face method turned into online learning method. As a result, college students began to complain about several things, such as network problems, difficulty in doing group discussions, until symptoms such as stress and anxiety appears when they have to doing many tasks and have to choose the priority first, this had an impact on students' mental health. The stress level of students during this pandemic has a huge impact on mental health. This correlational research aims to determine the relationship between stress levels during the COVID-19 pandemic and the anxiety of Unaya’s medical student with used cross-sectional design. Based on statistical results obtained pvalue = 0.837 (pvalue 0.05), it shows that was no significant correlation between stress levels during the Covid-19 pandemic and the anxiety of Unaya’s medical student.Keywords: Stress, COVID – 19, Anxiety